PENGARUH KAPASITAS SUMBER DAYA MANUSIA DAN PENGENDALIAN INTERN AKUNTANSI PADA PELAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH (SKPD) KABUPATEN GIANYAR - Ni Putu Riski Martini (Faculty of Economics and Business, Universitas Warmadewa, 2018)
Abstract The current government institutions must follow accounting developments because users of information, especially the public demand that accountability and transparency be done. Local governments are obliged to publish information in the financial statements as a basis for decision making. Thus, the published information should be useful to the users. Information will be useful if the information is understood and can be used by users and users to trust the information. This study aims to examine the effect of human resource capacity and internal control on the financial reporting of regional work units in Gianyar regency. Population in this research is all employee in SKPD Government of Gianyar regency with method of determination of saturated sample with criterion of determination of sample which will be used in this research is 32 office of Local Government Device Unit (SKPD) Gianyar which carry out accounting finance function. Data analysis technique which is used in this research is multiple linier regression analysis technique. Based on the results of the analysis conducted then obtained the conclusion that the variable capacity of human resources and internal control affects the financial reporting unit of work device area in Gianyar regency. Keywords: human resource capacity and internal control